2004
DOI: 10.1515/epoly.2004.4.1.182
|View full text |Cite
|
Sign up to set email alerts
|

Nafion-layered silicate nanocomposite membrane for fuel cell application

Abstract: Direct methanol fuel cells (DMFCs) using a proton exchange membrane as electrolyte is an attractive option for electricity generation. The most widely used membrane in the DMFC system is based on a perfluorinated polymer bearing sulfonic acid functions like Nafion ® . The latter combines chemical, mechanical and thermal stability and high protonic conductivity but shows elevated methanol permeability. We propose the preparation of a novel type of hybrid membranes to tentatively solve this problem. This innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Because polymers commonly used as fuel cell membranes are not able to disperse the native nanoclay properly [14], poly(vinyl alcohol), in which the nanofiller is easily exfoliated, has been chosen as a model membrane. However, the ionic conductivity of this type of membraneisintrinsically low and doping by phosphotungstic acid is required.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because polymers commonly used as fuel cell membranes are not able to disperse the native nanoclay properly [14], poly(vinyl alcohol), in which the nanofiller is easily exfoliated, has been chosen as a model membrane. However, the ionic conductivity of this type of membraneisintrinsically low and doping by phosphotungstic acid is required.…”
Section: Resultsmentioning
confidence: 99%
“…L/W is the anisotropy factor. In a previous study, we have shown that although nanoclays resist complete exfoliation within Nafion ® [14,15], the methanol permeability of this polymer is decreased by the multi-layered alumino-silicate. This preliminary observation is a strong incentive to model a situation in which the alumino-silicate would be completely delaminated within a polymer usable as a fuel cell membrane.…”
Section: Fig 1 the Typical Dispersion States Of A Nanoclay Within Amentioning
confidence: 86%
“…This trend remains unchanged even upon UV irradiation of the , and ammonium counter ions) showed a highest conductivity with the acid-activated MMT (H + counter ion) compared to MMT having Na + and ammonium counter ions due to the ease in mobility of the smaller counter ions (H + ion) (Fig. 22.16) [113]. Sulfonation of the nanoclay surface was also noted to increase the proton conductivity of the resulting membrane compared to the virgin Nafion and Nafion ® -unmodified Laponite nanocomposite due to the presence of the highly proton-conducting -SO 3 H group on the clay surface [94].…”
Section: Proton Conductivitymentioning
confidence: 92%
“…Addition of sulfonated MMT and Cloisite 30B to Nafion reduced the methanol and water permeability relative to the virgin Nafion due nm m to their well-dispersed morphology in Nafion [89,113]. However, poor polymer-filler interactions resulting in the void formation in the polymer-filler interface and inferior dispersion of unmodified MMT in Nafion reduced the barrier effect of Nafion-based composite towards methanol compared to the virgin Nafion ( Fig.…”
Section: Permeabilitymentioning
confidence: 96%
See 1 more Smart Citation